2011
DOI: 10.1128/jcm.05632-11
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year History of Transcription-Mediated Amplification-Based Trichomonas vaginalis Analyte-Specific Reagent Testing in a Subacute Care Patient Population

Abstract: A total of 7,899 specimens submitted for live clinical Trichomonas vaginalis analyte-specific reagent (ASR) screening from 2008 to 2010 were audited on the basis of patient gender, specimen source, molecular Neisseria gonorrhoeae and Chlamydia trachomatis results, and relative light unit (RLU) data yielded by T. vaginalis ASR. Only 1.4% of the screening was ordered by emergency department clinicians. The screening volume in 2010 was 126% higher than that in 2008. The proportions of annual female and male scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Therefore, comparison of performance characteristics by specimen source could not be accomplished in this retrospective assessment. Of further interest, previous studies in our female patient population demonstrated increased T. vaginalis detection from first-void urine specimens (25,35). We also show increased T. vaginalis detection from first-void urine compared to cervical specimens (P ϭ 0.04; Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, comparison of performance characteristics by specimen source could not be accomplished in this retrospective assessment. Of further interest, previous studies in our female patient population demonstrated increased T. vaginalis detection from first-void urine specimens (25,35). We also show increased T. vaginalis detection from first-void urine compared to cervical specimens (P ϭ 0.04; Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Prior to FDA clearance in 2011, T. vaginalis TMA was also commercially available as an ASR. Napierala et al (35) demonstrated progressively increased utilization of that assay over a 3-year interval. Should an analogous pattern be observed …”
Section: Discussionmentioning
confidence: 99%
“…In spite of trichomoniasis largely presenting as vulvovaginitis, T. vaginalis analyte-specific reagent (ASR)-derived data describe the value of endocervical samplings for molecular T. vaginalis detection (19,22,24). In addition, preliminary data suggest increased T. vaginalis detection from first-void urine specimens compared to that from vaginal and cervical specimens (1,21).…”
mentioning
confidence: 91%
“…However, sexually transmitted infection (STI) prevalence limitations were inherent to these two reports. Napierala et al (21) summarized operational characteristics of T. vaginalis ASR using a highprevalence STI metropolitan area. That study served as the basis for the presented investigation.…”
mentioning
confidence: 99%
“…A previous assessment of T. vaginalis TMA showed 100% molecular concordance between the data from vaginal saline suspension aliquots and endocervical specimens maintained in Aptima specimen transport tubes (7). In addition, Napierala et al (8) have shown equivalent T. vaginalis TMA detection rates from endocervical swabs and vaginal swabs in our population. This study was governed by the Wheaton Franciscan Healthcare Institutional Review Board.…”
mentioning
confidence: 75%